Fruit and Vegetable Value Chains in Benin: Identification of Intervention Entry Points - Fassinou Hotegni, Vodjo Nicodème; Salaou, M.; Godonou, M. (International Food Policy Research Institute, 2022)
This report produced by FRESH initiative partner Applied Horticultural Research and in-country partner University of Abomey Calavi provides an overview of fruit and vegetable value chains in Benin. The report characterizes the fruit and vegetable value chains in Benin through an in-depth review of the literature on postharvest and food security issues in order to set priorities for research and action in the fruit and vegetable sector in Benin and identify entry points for change. The present document presents the literature review on fruits and vegetables sector in Benin with a focus on post-harvest losses studies and interventions on fruits and vegetables. It identifies the need to generate new evidence on post-harvest loss, and safety of fruits and vegetables in different geographic areas of Benin and of specific value chains; design, pilot and scale innovations to reduce post-harvest losses and improve safety; and building awareness and sharing capacity.